Description and Demonstration Signals as Complements and Substitutes in an Online Market for Mental Health Care - Zhou, Junjie; Kishore, Rajiv; Amo, Laura; Ye, Cheng (MIS Quarterly, 2022)
Online markets for mental health care (OMMH) allow clients to connect remotely with counselors to receive psychological therapy. Rooted in signaling theory and in the specific context of an OMMH, we theorize relative credibility of signals as the boundary condition that determines whether the demonstration signal of responsiveness to client questions substitutes or complements the two description signals of professional qualifications and counseling style in predicting market demand for counselors from new clients in an OMMH. Based on a panel dataset of 823 observations from 309 counselors participating on YiXinLi, a leading OMMH in China, we tested our hypotheses using linguistic and sentiment analysis methods and zero-inflated negative binomial models. We found broad support for nine out of ten hypotheses. Findings are robust with respect to different measures of variables, potential endogeneity from the simultaneity of responsiveness and counselor demand, and potential selection bias from both observable and endogenous covariates. Our study extends the literature on signaling in online markets in the unique context of OMMH by showing that: (1) relative credibility of signals is the boundary condition that determines when a demonstration signal will complement and when it will substitute for a description signal, (2) previous clients’ feedback on counselors’ empathy and warmth was deemed not credible by new clients in the context of online counseling, and (3) responsiveness to client questions is the most influential predictor of market demand from new clients in an OMMH.